FAKTOR â FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK UMKM (Studi Pada Wajib Pajak Di Kabupaten Pati) - Adelia Anugrahi Kusuma, 12.05.52.0123; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2016)
This research to examined the effect of the payer taxes understanding, the fiskus service, awareness of pay, tax penalties and the payment mechanisms on tax compliance of UMKM. The population in this research is the payer taxes UMKM that have Identity Number of Payer Tax (NPWP) in Pati. The sampling method was conducted by sampling convience. Amount of samples processed as many as 87 samples and the analysis used by multiple regression metode. The results showed that the understanding of tax payers, the fiskus service, tax penalties and payment mechanisms that the effect on tax compliance UMKM. The opposite, awareness of pay taxes no effect on tax compliance UMKM.Keywords:Â Understanding The Tax Payers, The Fiskus Service, Awareness of Pay, Tax Penalties, The Payment Mechanisms of Taxes and Tax Payer Compliance UMKM